Expanding the Functional Scope of the Fmoc‐Diphenylalanine Hydrogelator by Introducing a Rigidifying and Chemically Active Urea Backbone Modification. Issue 12 (19th April 2019) - Basavalingappa, Vasantha; Guterman, Tom; Tang, Yiming; Nir, Sivan; Lei, Jiangtao; Chakraborty, Priyadarshi; Schnaider, Lee; Reches, Meital; Wei, Guanghong; Gazit, Ehud
Abstract: Peptidomimetic low‐molecular‐weight hydrogelators, a class of peptide‐like molecules with various backbone amide modifications, typically give rise to hydrogels of diverse properties and increased stability compared to peptide hydrogelators. Here, a new peptidomimetic low‐molecular‐weight hydrogelator is designed based on the well‐studied N ‐fluorenylmethoxycarbonyl diphenylalanine (Fmoc‐FF) peptide by replacing the amide bond with a frequently employed amide bond surrogate, the urea moiety, aiming to increase hydrogen bonding capabilities. This designed ureidopeptide, termed FmocPheNHCONHPheOH (Fmoc‐FuF), forms hydrogels with improved mechanical properties, as compared to those formed by the unmodified Fmoc‐FF. A combination of experimental and computational structural methods shows that hydrogen bonding and aromatic interactions facilitate Fmoc‐FuF gel formation. The Fmoc‐FuF hydrogel possesses properties favorable for biomedical applications, including shear thinning, self‐healing, and in vitro cellular biocompatibility. Additionally, the Fmoc‐FuF, but not Fmoc‐FF, hydrogel presents a range of functionalities useful for other applications, including antifouling, slow release of urea encapsulated in the gel at a high concentration, selective mechanical response to fluoride anions, and reduction of metal ions into catalytic nanoparticles. This study demonstrates how a simple backbone modification can enhance the mechanical properties and functional scope of a peptide hydrogel. Abstract : A rigid and multifunctional peptidomimetic hydrogel, obtained by replacing the amide bond of the well‐studied hydrogelator Fmoc‐diphenylalanine (Fmoc‐FF) with a urea group, presents biocompatibility, selective mechanical response to anions, metal reduction capabilities, urea storage and slow release, and antifouling behavior. These functional properties are not available in the unmodified Fmoc‐FF hydrogel.